Improving Energy Efficiency with Energy Recovery for Propylene Production - Hurairah, Andi Nadhif Athallah; Arkajaya, Danu Pasa; Ramadhani, Tenisyah; Fahrezi, Virgi Achmad (Journal of Chemical Engineering Research Progress, 2024)
Propylene production through the metathesis of 2-butene is a well-established method. However, energy efficiency in this process remains an area of improvement. This study focuses on optimizing energy consumption by integrating heat recovery and reducing the reliance on external energy sources. Simulations were conducted using Aspen HYSYS V11 to compare the basic and modified processes. Modifications included utilizing heat from condensers and coolers to power compressors and heaters, eliminating redundant heating units. Thermodynamic analyses confirmed the endothermic nature of the reactions. Results indicated a significant reduction in total heat flow, from 2.983×108 kJ/h to 1.564×108 kJ/h, leading to improved specific energy consumption. With a production capacity of 15,400 tons/year, the optimized process demonstrated enhanced energy efficiency and sustainability. This study highlights the potential of process modifications to achieve energy savings, lower production costs, and minimize environmental impact in the chemical industry. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).